‘Hot phase’ clinical presentation in arrhythmogenic cardiomyopathy - Bariani, Riccardo; Cipriani, Alberto; Rizzo, Stefania; Celeghin, Rudy; Bueno Marinas, Maria; Giorgi, Benedetta; De Gaspari, Monica; Rigato, Ilaria; Leoni, Loira; Zorzi, Alessandro; De Lazzari, Manuel; Rampazzo, Alessandra; et al. (Europace (London, England), 2021)
Abstract Aims The aim of this study is to evaluate the clinical features of patients affected by arrhythmogenic cardiomyopathy (AC), presenting with chest pain and myocardial enzyme release in the setting of normal coronary arteries (‘hot phase’). Methods and results We collected detailed anamnestic, clinical, instrumental, genetic, and histopathological findings as well as follow-up data in a series of AC patients who experienced a hot phase. A total of 23 subjects (12 males, mean age at the first episode 27 ± 16 years) were identified among 560 AC probands and family members (5%). At first episode, 10 patients (43%) already fulfilled AC diagnostic criteria. Twelve-lead electrocardiogram recorded during symptoms showed ST-segment elevation in 11 patients (48%). Endomyocardial biopsy was performed in 11 patients, 8 of them during the acute phase showing histologic evidence of virus-negative myocarditis in 88%. Cardiac magnetic resonance was performed in 21 patients, 12 of them during the acute phase; oedema and/or hyperaemia were detected in 7 (58%) and late gadolinium enhancement in 11 (92%). At the end of follow-up (mean 17 years, range 1–32), 12 additional patients achieved an AC diagnosis. Genetic testing was positive in 77% of cases and pathogenic mutations in desmoplakin gene were the most frequent. No patient complained of sustained ventricular arrhythmias or died suddenly during the ‘hot phase’. Conclusion ‘Hot phase’ represents an uncommon clinical presentation of AC, which often occurs in paediatric patients and carriers of desmoplakin gene mutations. Tissue characterization, family history, and genetic test represent fundamental diagnostic tools for differential diagnosis.